Multivariate analysis of oil palm germplasm for vegetative and bunch yield traits - Bhagya, H.P.; Gangadharappa, P.M.; Kalyanababu, B.; Naika, Mahantesh B. N.; Satish, D.; Naik, R.B. (Journal of Plantation Crops, 2019)
Multivariate analysis of oil palm germplasm for vegetative and bunch yield traits